Implementasi Education Management Information Sistem (EMIS) Dalam Pengambilan Kebijakan Pendidikan - Muslim, Muslim; Firdaus, Muhammad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The research in this thesis is motivated by the development of technology and information as a data collection base that has a very important role in supporting the achievement of educational goals. Information technology based on data collectors has an important object in advancing educational goals. The existence of EMIS is used as one of the main bases in making educational policies at Madrasah Tsanawiyah Darul Aitam, so it is hoped that all incoming data will be more updated and accurate. The purpose of this study is to describe, 1) Strategic steps to implement EMIS in MTs Darul Aitam Tlambah in education policy-making 2) The impact of EMIS on education policy-making in Madrasah Tsanawiyah Darul Aitam Tlambah. The approach used in this study is qualitative descriptive with the type of case study. The researcher used observation, interview, and documentation data collection techniques. The data analysis used is data collection, data condensation, data presentation, and conclusion drawn/verification. The validity of the data used is source triangulation and technique triangulation. Conclusions obtained from the results of this study 1) The strategic steps of implementing EMIS at MTs Darul Aitam in making education policies in accordance with the EMIS guidelines, namely registration, login, institutional updates, old student updates, new student input, GTK updates, infrastructure updates, and BAP upload/download. The policy-making process is by identifying problems, searching for information, evaluating alternatives, making policies, and behaviors after education policy-making. Such as the fulfillment of teaching hours. 2) The impact resulting from EMIS on education policy-making, namely, can improve the performance of EMIS management in determining policies related to education financing such as School Operational Assistance (BOS) and realizing the effectiveness of achieving the smart indonesia program (PIP). Supporting factors for the establishment of good cooperation between operators and madrasah heads, laptop wifi facilities, inhibiting factors, unreadable NIK error system.